2006
DOI: 10.1007/s11274-006-9220-7
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of antifouling compounds from the marine bacterium, Shewanella oneidensis SCH0402

Abstract: Two compounds, 2-hydroxymyristic acid (HMA) and cis-9-oleic acid (COA), were isolated from a chloroform extract of the marine bacterium, Shewanella oneidensis SCH0402. In a spectrophotometerbased chemotaxis assay, HMA completely eliminated the optical density (OD) of Alteromonas marina SCH0401 and Bacillus atrophaeus SCH0408, motile, fouling bacteria, at 100 and 1000 lg ml -1 , respectively. COA similarly decreased the OD of A. marina and B. atrophaeus by 100% at 1000 lg ml -1 . The commercially available, hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 23 publications
0
21
0
2
Order By: Relevance
“…These compounds inhibited settlement of zoospores of U. pertusa and the diatom Navicula annexa. The marine bacterium Shewanella oneidensis SCH0402 produced 2-hydroxymyristic acid and cis-9-oleic acid, which inhibited germination of spores of U. pertusa (Bhattarai et al 2007). In field bioassays, these compounds were as efficient as the toxic AF compound tributyltin oxide.…”
Section: Antialgal Activity Heterotrophic Bacteriamentioning
confidence: 99%
“…These compounds inhibited settlement of zoospores of U. pertusa and the diatom Navicula annexa. The marine bacterium Shewanella oneidensis SCH0402 produced 2-hydroxymyristic acid and cis-9-oleic acid, which inhibited germination of spores of U. pertusa (Bhattarai et al 2007). In field bioassays, these compounds were as efficient as the toxic AF compound tributyltin oxide.…”
Section: Antialgal Activity Heterotrophic Bacteriamentioning
confidence: 99%
“…More importantly, antifouling coatings containing 10% 9-Z-oleic acid were able to reduce the attachment of micro-and macro-foulers for about 1.5 years. [28,29] Alkylated butenolides were also a class of metabolites from marine bacteria Streptomyces sp., which showed potent antifouling activity against the larvae of fouling organisms with very weak toxicity. The study of structure-activity relationships revealed that the 2-furanone ring was essential for the activity and lipophilicity obviously influenced their antifouling activities.…”
Section: Discussionmentioning
confidence: 99%
“…Palmitic acid, isolated from the brown alga Sargussum muticum, and 2-hydroxymyristic acid and (9Z)-oleic acid, derived from the marine bacterium Shewanella oneidensis, inhibit spores of U. pertusa. 39,40) In the present experiment, the antifouling activity of commercial free fatty acids was determined. It showed less activity than the glycoglycerolipids, suggesting that glycolycerolipids are responsible for the antifouling activity, not the fatty acids alone.…”
Section: Positionmentioning
confidence: 99%